Non-Coding RNAs Steering the Senescence-Related Progress, Properties, and Application of Mesenchymal Stem Cells - Cai, Jingyi; Qi, Hexu; Yao, Ke; Yao, Yang; Jing, Dian; Liao, Wen; Zhao, Zhihe (Frontiers in Cell and Developmental Biology, 2021)
Thirst to postpone and even reverse the age progress has never quenched for all these decades. Unequivocally, mesenchymal stem cells (MSCs), with extraordinary abilities as self-renewal and multi-directional differentiation, deserve the limelight in this topic. Though having several affable clinical traits, MSCs going through senescence would, on one hand, contribute to age-related diseases, on the other hand, lead to compromised or even counterproductive therapeutical outcomes. Notably, increasing evidence suggests that non-coding RNAs (ncRNAs) could give sprightliness to various regulatory processes. With even a slight dip or an uptick of expression, ncRNAs would make a dent to or even overturn cellular fate. Thereby, a systematic illustration of ncRNAs identified so far to steer MSCs during senescence is axiomatically in an urgent need, yet remains void. In this review, we introduce the general properties and mechanisms of senescence and its relationship with MSCs and sketch the ncRNAs playing in the cellular senescence of MSCs. It is then followed by the elucidation of ncRNAs embodied in extracellular vesicles connecting senescent MSCs with other cells and progress in and beyond the skeleton system. Last, we provide a glimpse into the clinical methodologies of ncRNA-based therapies in MSC-related fields. Hopefully, the panorama of senescence and MSCs would be displayed one day and our work would provide a glimpse or a stepping-stone to that future.